The First Encounter : Framing Research Collaboration Through Screens - Bjørn Vedel , Jane (STS Encounters, 2011)
Much work in Science and Technology Studies (STS) assumes that scientists enter into research collaborations as entities characterized by difference. It is assumed that in order to collaborate these differences must be aligned. In this paper, I investigate the intriguing role of difference in collaboration by looking at an empirical case of research collaboration between a pharmaceutical company and a not-for-profit research organization. The case raises the question of whether sameness in collaboration is always necessary and, consequently, whether difference as such is a hindrance to research collaboration. I conclude the paper by suggesting that if collaboration is in fact not held back by dissimilarities this suggests a need to rethink the dynamics of science-industry relations.